2013
DOI: 10.3174/ajnr.a3724
|View full text |Cite
|
Sign up to set email alerts
|

Semiautomated Volumetric Measurement on Postcontrast MR Imaging for Analysis of Recurrent and Residual Disease in Glioblastoma Multiforme

Abstract: BACKGROUND AND PURPOSE:A limitation in postoperative monitoring of patients with glioblastoma is the lack of objective measures to quantify residual and recurrent disease. Automated computer-assisted volumetric analysis of contrast-enhancing tissue represents a potential tool to aid the radiologist in following these patients. In this study, we hypothesize that computer-assisted volumetry will show increased precision and speed over conventional 1D and 2D techniques in assessing residual and/or recurrent tumor. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 26 publications
4
64
0
Order By: Relevance
“…Increased interest in semiautomated computer segmentation in the analysis of brain tumors, coupled with validation, may circumvent some subjectivity in delineating the image-definable components of glial tumors. 39 Standardization of segmentation techniques is expected to improve the utility of quantitative measurements. Furthermore, in most studies, a range of values was observed among patients.…”
Section: Discussionmentioning
confidence: 99%
“…Increased interest in semiautomated computer segmentation in the analysis of brain tumors, coupled with validation, may circumvent some subjectivity in delineating the image-definable components of glial tumors. 39 Standardization of segmentation techniques is expected to improve the utility of quantitative measurements. Furthermore, in most studies, a range of values was observed among patients.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, this semi-automated algorithm combines the region-based active contours and a level set approach and has been shown to provide for reproductive assessment of enhancing tumor burden in postoperative GBM patients. 8 All measurements were performed with correlation to precontrast T1 images to avoid T1 shortening effects from postsurgical changes (for example, blood products).…”
Section: Radiographic Imaging and Assessment Of Extent Of Resectionmentioning
confidence: 99%
“…Various imaging techniques of transformation, filtering and segmentation 11,12 allow us to analyze MRI in a comprehensive approach beyond eyesight. Jones et al 13 applied whole-brain diffusion tensor imaging segmentation to delineate tumour volume and improved the accuracy of diagnosis, while Chow et al 14 used reliable semi-automated segmentation to monitor tumour progression in patients with GBM. Furthermore, computerassisted assessment could identify GBM molecular subtypes even without biopsy.…”
Section: Introductionmentioning
confidence: 99%